Preoperative Risk Stratification of Right Ventricular Function Utilizing Cardiac Magnetic Resonance Imaging Compared With Echocardiographic and Hemodynamic Parameters. Issue 5 (May 2020) - Avery, Ryan; Ebong, Imo; Skaria, Rinku; Day, Kevin; Miller, Christopher; Juneman, Elizabeth; Oliva, Isabel; Friedman, Mark; Maltais, Simon; Khalpey, Zain
Abstract : Accurate right ventricle functional analysis prior to mechanical circulatory support continues to be valuable for preoperative stratification of patients at risk for developing right ventricular (RV) failure. While cardiac magnetic resonance imaging (CMR) remains the gold standard, CMR is limited by availability and patient-specific contraindications. Further investigation of other imaging modalities would be beneficial as it may serve as a surrogate to identifying RV systolic dysfunction. A single-center, retrospective study including 29 patients with advanced heart failure was performed. All patients underwent ventricular functional analysis with both CMR and echocardiography, and 19 patients underwent right heart catheterization. Predictability with multimodal assessment of RV function was determined using logistic regression methods. Of the 29 participants, 10 had severe RV dysfunction. Tricuspid annular plane of systolic excursion was a modest predictor of RV dysfunction with odd ratio (OR) of 0.07 (0.01–0.72) and c-statistic of 0.79. Invasive hemodynamic measurement of cardiac index by thermodilution method was also predictive of RV dysfunction but failed to reach statistical significance (OR of 0.03, <0.001–1.28) with c-statistic of 0.83. The role of invasive hemodynamic data in predicting RV function compared with CMR should be further explored among patients with advanced heart failure.